AL-QUR’AN DAN KECEDASAN MANUSIA (Kajian tentang Kecerdasan Intelektual (IQ), Kecerdasan Emosional (EQ) dan Kecerdasan Spiritual (SQ) - Saihu, Made (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2022)
This study discusses the typology of human intelligence, they are intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ). IQ is influenced by understanding and reasoning in the field, shape by figure, language, numeric abilities. EQ shows the ability to feel about oneself and the feelings of others. SQ, refers to the non-material dimension, which is likened to a diamond that has not been honed and is owned by every human being. Through this understanding, this literature study emphasizes the importance of balancing the three human intelligences. Although IQ is the type of intelligence that was first recognized by humans, this intelligence has not shown the potential intelligence that humans have. Here humans are obliged to develop their EQ and SQ simultaneously. If EQ is related to feelings and is practical, then SQ is spiritual and reflective. In other words, EQ gives or leads to know-how, while SQ directs to know-why. The integration of these three intelligences will direct humans to increase morals and dignity. This reality must be practiced by every human being in order to create awareness of the social reality they are facing. In addition, through balancing these three intelligences, it can produce students who are not only smart or intelligent but can produce happy children. A study that seeks to optimize human potential through the balance of the three intelligences possessed by humans